Slow-light photonic crystal devices for high-speed optical signal processing - Brosi, Jan-Michael (Karlsruhe Series in Photonics & Communications / Universität Karlsruhe (TH), Institute of High-Frequency and Quantum Electronics (IHQ), 2009)
This book discusses design, modeling, and the characterization of slow-light photonic crystal waveguides. Guidelines are developed to obtain slow-light waveguides with broadband characteristics and with low disorder-induced losses. Three functional devices are proposed and studied: A tunable dispersion compensator, a tunable optical delay line, and a high-speed electro-optic modulator. Optical and microwave measurements confirm the designs.